Design of a Web-Based Health Information System to Support a Teaching Factory in Health Information Management of PSDKU Ngawi - Wicaksono, Kurniawan Erman; Nurmawati, Ida; Supriyanto, Budi Fajar; Hanifa, Salihati; Nurjihan, Ikha (Indonesian Journal Publisher, 2025)
Health services are among the most needed services by the community. In Ngawi Regency, Indonesia, residents often struggle to access vital health service information. With the advancement of technology, such as web-based health service information systems, it becomes easier for the community to access information about health services. The design of a web-based health service information system aims to support the establishment of a pioneering teaching factory for the Health Information Management study program. This research employs the SDLC (System Development Life Cycle) software development method using the prototype model. The stages of the system design and development include quick plan, modelling, quick design, construction of prototype, deployment, delivery and feedback, and communication. The research results indicate that the web-based health service information system can facilitate the Ngawi community and its surroundings in accessing health service information, registering online, conducting self-health checks, consulting with health personnel via a WhatsApp link available on the web, serving as a health promotion media, and enabling users or health personnel to utilize patient data stored in the system database as a learning support tool. Based on the research findings, the system significantly enhances community access to health services and streamlines health management processes for users.